Massive Nitrogen Loss Over the Western Indian Continental Shelf During Seasonal Anoxia: Evidence From Isotope Pairing Technique - Sarkar, Amit; Naqvi, Syed Wajih Ahmad; Lavik, Gaute; Pratihary, Anil; Naik, Hema; Shirodkar, Gayatri; Kuypers, Marcel M. M. (Frontiers in Marine Science, 2020)
The western Indian continental shelf houses the world's largest naturally-formed coastal low-oxygen zone that develops seasonally during the summer monsoon. We investigated multiple reductive nitrogen transformation pathways and quantified their rates in this system through anaerobic incubations with additions of 15N-labeled substrates during the anoxic period for three consecutive years (2008 to 2010). Addition of 15N labeled ammonium (15NH4+) resulted in low to moderate anaerobic ammonia oxidation (Anammox) rates in about half of our incubations from the oxygen depleted waters. In contrast, incubations with labeled nitrite (15NO2-) led to large production of 30N2 over 29N2 in all incubation experiments, indicating denitrification to be the dominant N-loss pathway. Rates of dissimilatory nitrate/nitrite reduction to ammonia (DNRA) were found to be highly variable and were lower by an order of magnitude than the denitrification rates. Extrapolation of average rates over the sampling periods and volume of anoxic waters showed large nitrogen removal (3.70 to 11.1 Tg yr-1) which is about three times as high as the previously reported estimate (1.3 to 3.8 Tg yr-1). Despite the small area it occupies, this shallow seasonal anoxic zone may account for as much as 20-60% the of the total annual fixed nitrogen loss in the perennial oxygen minimum zone of the Arabian Sea.